Aplikasi Model Rasch dalam Pengembangan Instrumen Deteksi Dini Postpartum Depression - Ardiyanti, Difa; Dinni, Siti Muthia (Faculty of Psychology, Universitas Gadjah Mada, 2018)
After giving birth, women will face a lot of challenge as a mother. That situation demands an adaptation process so that it is risky for women to diagnosed postpartum depression (PPD) disorder. Late detection and treatment may endanger the lives of the mother and baby. This condition indicates that PPD is a serious long term mental health problem and related to mother-child safety issues. Unfortunately, in Indonesia, the postpartum depression detection tool has never been developed. This study developed an early detection tool of postpartum depression (PPD) using the Rasch model which considered having advantages compared to the classical test theory. The subjects were 78 women who had just given birth last 2-6 weeks. Based on the results of the analysis using Winsteps, 13 items of 17 items met the grain-model fit index, with an alpha reliability coefficient of 0,90. Overall, it can be concluded that this early detection instrument of postpartum depression has good psychometric properties. Hence, it can be used for early assessment and research.Â Abstrak : Tingginya tantangan seorang ibu setelah melahirkan menuntut sebuah proses adaptasi yang besar sehingga berisiko mencetus gangguan depresi setelah melahirkan (postpartum depression atau PPD). Deteksi dan penanganan yang terlambat dapat membahayakan nyawa ibu dan bayinya. Kondisi ini menunjukkan bahwa PPD merupakan permasalahan kesehatan mental keluarga serius dalam jangka panjang dan terkait dengan isu keselamatan ibu-anak. Sayangnya, di Indonesia, alat deteksi PPD belum pernah dikembangkan. Penelitian ini bertujuan untuk mengembangkan instrumen deteksi dini postpartum depression (PPD) menggunakan model Rasch, suatu pendekatan yang dipandang memiliki keunggulan dibanÂdingkan teori tes klasik. Subjek penelitian adalah 78 wanita yang baru saja melahirkan 2-6 minggu terakhir. Berdasarkan hasil analisis menggunakan program Winsteps, didapatkan 13 aitem (dari 17 aitem)yang memenuhi tingkat kesesuaian butir-model, dengan koefisien reliabilitas alpha 0,90. Secara keseluruhan, dapat disimpulkan bahwa instrumen deteksi dini postpartum depression ini memiliki properti psikometris yang baik sehingga dapat digunakan untuk asesmen awal maupun penelitian.